Association of Variables of Coagulation, Fibrinolysis and Acute-phase with Atherosclerosis in Coronary and Peripheral Arteries and those Arteries Supplying the Brain - Heinrich, Jürgen; Schulte, Helmut; Schönfeld, Rainer; Köhler, Ekkehart; Assmann, Gerd (Thrombosis and Haemostasis, 1995)
We investigated the vessel status of coronary and peripheral arteries and those arteries supplying the brain in 929 consecutive male patients admitted to a coronary rehabilitation unit. The severity of coronary atherosclerosis was scored using coronary angiography. Changes in extracranial brain vessels and manifest cerebrovascular disease (CVD) were determined by B-mode ultrasound and Doppler examination. Peripheral arterial disease (PAD) was diagnosed using base-line and stress oscillography. We assessed variables of coagulation, fibrinolysis, and the acute phase response.There was a significant increase in plasma fibrinogen, plasminogen, d-dimer and C-reactive protein (CRP) with increasing severity of coronary heart disease. Compared to men with unaffected arteries, men with 3 diseased coronary arteries had 58% greater d-dimer concentrations. Patients with CVD and PAD, respectively, also had significantly higher fibrinogen, d-dimer and CRP concentrations. We did not find an association between plasminogen activator inhibitor activity and the severity of coronary atherosclerosis.In conclusion, plasma fibrinogen, d-dimer and CRP concentrations were significantly related to atherosclerosis in the coronary, peripheral and extracranial brain arteries.